Hubungan Tingkat Stres Terhadap Kadar Glukosa Darah Puasa pada Laki-Laki Penderita Obesitas Sentral di Lingkungan Universitas Lampung - Khalisah Nurjihany Salsabila; Khairun Nisa Berawi; Dwita Oktaria (Medula, 2022)
The incidence of Diabetes Mellitus (DM) in the world and in Indonesia continues to increase. One factor that can affect high blood glucose levels and end up being DM is psychological stress. Patients with central obesity are more vulnerable and have a higher risk of experiencing stress caused by various psychological and emotional factors. The occurrence of stress will cause the activation of the Corticotropic-Releasing Hormone (CRH)-Adrenocorticotropic Hormone (ACTH)-cortisol hormone system which has a direct effect on increasing glucose levels in the blood (hyperglycemia) and if the condition continues, it will increase the risk of DM disease. Observational analytic method with a cross-sectional approach was used in this study. The study sample consisted of 82 patients with central obesity in the University of Lampung environment, with a consecutive sampling method. This research was conducted by filling in and direct interviewing the Perceived Stress Scale (PSS)-10 questionnaire and measuring fasting blood glucose levels in all the academic communities on men with central obesity at the University of Lampung. The results of the univariate analysis of the research sample were dominated by the age group of 18-25 years; the stress level was in the moderate category; with uncontrolled fasting blood glucose levels. The results of bivariate analysis with Chi-Square test showed p-value = 0.001 (p-value <0.05). There is a relationship between stress level and fasting blood glucose in men with central obesity at the University of Lampung.